Evaluation of livestock’s hide and skin marketing in Adamawa State, Nigeria - Ja’afar-Furo, Muhammad R.; Calvin, Kemuel; Abdullahi, A’ishatu (Journal of Agriculture and Natural Resources, 2021)
This study evaluated hide and skin marketing in Adamawa State, Nigeria, with the aim of describing the socioeconomic variables of the marketers, determining the marketing efficiency and major socioeconomic factors that influenced participation in the area. Purposive and simple random sampling methods were used in the selection of four large and small ruminant markets, and 120 hide and skin marketers, respectively. Descriptive statistics, Marketing Efficiency (ME) and regression analysis were employed in the analyses of data. Results show that all the marketers were males (100%) and married (66.67%) within middle-aged group. A larger proportion (40.00%) had secondary school education and fairly experienced in the business. The most popular (51.67%) channel of hide and skin marketing was producer-rural collector-urban collector-wholesaler-tanneries, with a very efficient marketing (178.52%). Further, the level of education and marketing experience of marketers and the average purchasing price of hide and skin were found to heavily influence the marketing output in the area. The major challenges experienced were insufficiency of capital (88.33%), multiple taxations on transit (71.66%) and quality deterioration (63.33%). It is recommended that institutions that intend to improve on hide and skin marketing in the State and areas with similar economic terrains should resolve the aspect of inadequacy of funds, minimise tax on products, and employ efficient extension services to tackle spoilage.